Suppression of lipopolysaccharide-induced antiviral transcription factor (STAT-1 and NF-κB) complexes by antibody-dependent enhancement of macrophage infection by Ross River virus - Mahalingam, Surendran (The National Academy of Sciences, 2002)
Subneutralizing concentrations of antibody may enhance virus infection by bringing the virus–antibody complex into contact with the cell surface Fc receptors; this interaction facilitates entry of virus into the cell and is referred to as antibody-dependent enhancement (ADE) of infection. Northern analysis of macrophage RNA demonstrated that ADE infection by the indigenous Australian alphavirus Ross River (RRV-ADE) ablated or diminished message for tumor necrosis factor α (TNF-α), nitric-oxide synthase 2 (NOS2), and IFN regulatory factor 1 (IRF-1), as well as for IFN-inducible protein 10 (IP-10) and IFN-β; the transcription of a control gene was unaffected. Additionally, electrophoretic mobility-shift assay (EMSA) studies showed that transcription factor IFN-α-activated factor (AAF), IFN-stimulated gene factor 3 (ISGF3), and nuclear factor-κB (NF-κB) complex formation in macrophage nuclear extracts were specifically suppressed post-RRV-ADE infection, emphasizing the capacity for ADE infections to compromise antiviral responses at the transcriptional level. The suppression of antiviral transcription factor complexes was shown to depend on replicating virus and was not simply a result of general antibody–Fc–receptor interaction. Although only a minority of cells (≈15%) were shown to be positive for RRV by immunostaining techniques post ADE, molecular (RT-PCR) analysis showed that unstained cells carried RRV-RNA, indicating a higher level of viral infectivity than previously suspected. Electron microscopy studies confirmed this observation. Furthermore, levels of cellular IL-10 protein were dramatically elevated in RRV-ADE cultures. This evidence demonstrates that RRV can potently disrupt the activation of specific antiviral pathways via ADE infection pathways, and may suggest a significant mechanism in the infection and pathogenesis of other ADE viruses.